Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/nar/gky1319
|View full text |Cite
|
Sign up to set email alerts
|

Broad range of missense error frequencies in cellular proteins

Abstract: Assessment of the fidelity of gene expression is crucial to understand cell homeostasis. Here we present a highly sensitive method for the systematic Quantification of Rare Amino acid Substitutions (QRAS) using absolute quantification by targeted mass spectrometry after chromatographic enrichment of peptides with missense amino acid substitutions. By analyzing incorporation of near- and non-cognate amino acids in a model protein EF-Tu, we show that most of missense errors are too rare to detect by conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 70 publications
2
50
0
2
Order By: Relevance
“…Failing to discriminate against incorrect aa-tRNA results in missense errors of translation. Generally, the fidelity of decoding is very high, with a frequency of missense errors in the range from <10 −7 to 10 −4 per codon depending on the type of mismatch and the position of the amino acid in the protein (1)(2)(3)(4). At the end of the open reading frame, stop codons (UAA, UAG and UGA) are recognized by termination (release) factors (RF1 and RF2 in bacteria or eRF1 in eukaryotes).…”
Section: Introductionmentioning
confidence: 99%
“…Failing to discriminate against incorrect aa-tRNA results in missense errors of translation. Generally, the fidelity of decoding is very high, with a frequency of missense errors in the range from <10 −7 to 10 −4 per codon depending on the type of mismatch and the position of the amino acid in the protein (1)(2)(3)(4). At the end of the open reading frame, stop codons (UAA, UAG and UGA) are recognized by termination (release) factors (RF1 and RF2 in bacteria or eRF1 in eukaryotes).…”
Section: Introductionmentioning
confidence: 99%
“…Modern organisms transfer information from nucleic acid genes into functional proteins with very high accuracy. Error rates per amino acid monomer, ε, are of order 10 −4 or 10 −5 , sometimes even smaller [ 54 ]. Base pairing makes replication inherently accurate enough that the low cardinality of the nucleotide alphabet (n = 4) simplifies the problem of preserving the large body of template information required to code proteins with high functional specificity: any improvement in nucleotide discrimination has a close to threefold effect on the accuracy of codon replication.…”
Section: Discussionmentioning
confidence: 99%
“…Position 1 wobbling occurs not only in stop codons but also in sense codons, such as the misreading of arginine C GU/ C GC codons as cysteine U GU/ U GC codons [35, 36]. By using the prokaryote ortholog of elongation factor Tu (EF-Tu) for targeted mass spectrometry, it has been reported that even position 2 can be misdecoded by noncognate tRNAs, as illustrated by the detection of the arginine C G U codon misdecoded by tRNA G A G -Leu [5]. Thus, substantial misdecoding at all three positions is possible [2, 5] (Table 1).…”
Section: Trna Wobbling At Three Codon Positions Compromises the Fidelmentioning
confidence: 99%
“…Deciphering mRNA codons by transfer RNAs (tRNAs) in the ribosome involves Watson-Crick base pairing [1]. However, the translation machinery is not always perfect, and errors in the amino acid composition may occur [25]. The general error rates of genomic replication (about 10 −8 ) are estimated to be approximately 10,000-fold lower than those of protein synthesis (about 10 −4 ), and thus in most instances mRNA translation is the key process contributing to inaccuracy of the cellular proteome [6].…”
Section: Introductionmentioning
confidence: 99%